Green synthesis of gold nanoparticles using Sambucus ebulus fruit extract, characterization, and antileishmanial, antibacterial, antioxidant, and photocatalytic activities - Ebrahimzadeh, Mohammad Ali; Alizadeh, Seyedeh Roya; Hashemi, Zahra (European Journal of Chemistry, 2023)
In this study, gold nanoparticles were synthesized using the fruit extract of Sambucus ebulus (S. ebulus) as a reducing, capping, and stabilizing agent. Biogenic synthesis of gold nanoparticles (Au nanoparticles) was accomplished using S. ebulus fruit extract in the presence of hydrogen tetrachloroaurate(III) trihydrate at a temperature of 65 °C and the solution stirred at 400 rpm. The characterization of the synthesized nanoparticles (SE-AuNPs) was performed using different analytical methods, such as scanning electron microscopy (FE-SEM), energy dispersion X-ray spectroscopy (EDS), Fourier transform infrared (FT-IR), X-ray diffraction analysis (XRD), and UV-vis spectroscopy. A strong absorption peak at 565 nm confirmed the formation of the gold nanoparticle. On the basis of the electron microscopy results, AuNPs were mostly spherical with an average size of 116.2 nm. The cubic crystalline structure of the prepared nanoparticles was confirmed using the XRD pattern and the average crystallite size was obtained at 28.471 nm. FT-IR analysis confirmed the presence of functional groups in the plant extract for the synthesis of nanoparticles. SE-AuNPs showed good antibacterial activity against Gram-positive and Gram-negative bacteria tested and exhibited potent antileishmanial activity. Furthermore, SE-AuNPs showed excellent antioxidant activity that inhibited DPPH radicals with an IC50 value of 21.976 µg/mL. The prepared AuNPs acted to degrade methyl orange (MO), which was performed in sodium borohydride and visible light.